Pendampingan Penyusunan Media Pembelajaran Berbasis Articulate Storyline 3 (As-Three) dalam Rangka Mengoptimalkan Implementasi Kurikulum Merdeka - Rufiana, Intan Sari; Arifin, Slamet; Ratna Ekawati, Ratna Ekawati; Mashfufah, Aynin; Randy, Mohammad Yusuf; Amaliya, Fierda Nursitasari (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2025)
The implementation of the independent curriculum in 2024 still leaves a number of problems, including the low ability of teachers to compile interactive learning media and teaching modules. For this reason, efforts are needed to assist teachers in compiling interactive learning media. The method used in this activity is Participatory Action Research (PAR). Participatory Action Research (PAR) is a collaborative approach that emphasizes the active involvement of participants. The participants involved in this activity were 20 teachers consisting of 6 men and 14 women at SDN Lesanpuro 1 Malang. The results showed that satisfaction was in the high category, with an average score ranging from 4.59 to 4.85; effectiveness was in the high category with an average score ranging from 4.59 to 4.85. This satisfaction and effectiveness consist of several aspects such as the usefulness of activities, mastery of knowledge, and implementation in learning.